A European Enlightenment in the Promised Land? The Jewish Kulturkampf at the Turn of the Twentieth Century. Issue 7 (16th November 2020) - Feiner, Shmuel
ABSTRACT: This article discusses the European Kulturkampf in the nineteenth century from the points of view of the Russian Hebrew writer Judah Leib Gordon and the founding father of the Zionist movement Theodor Herzl. Gordon's literary outlook emphasizes the tension between the traditional Jewish religious leadership and the maskilim as an instance of the sweeping all-European Kulturkampf phenomenon, in which the problem of the rabbis was the last issue that had not yet been solved. He believed that the return of the Jews to the Land of Israel, without the elimination of the rabbis' authority, carried serious dangers. In his dystopian feuilleton published in 1885 depicting the future Jewish state, he argued that the victory of liberalism was a historical necessity in order to avoid a radical orthodox and nationalistic hegemony. Like Gordon before him, Herzl feared that losing the basic humanistic principles of the Enlightenment the Jews had acquired in Europe would be one of the outcomes of their settling in the Land of Israel. In his 1902 utopian novel Altneuland he declared: "Stand by the principles that have made us great: Liberalism, Tolerance, Love of Mankind. Only then will Zion be truly Zion." Gordon and Herzl both expressed their concerns in their fictional works, probably wishing that these would serve only as warning signs.